Propagation of the pulsed electron beam of nanosecond duration in gas composition of high pressure; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Kholodnaya G. E. Galina Evgenievna; Sazonov R. V. Roman Vladimirovich; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich (2015, 2015)
Title screen